The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1007/s00335-013-9456-0
|View full text |Cite
|
Sign up to set email alerts
|

High-fat feeding rapidly induces obesity and lipid derangements in C57BL/6N mice

Abstract: C57BL/6N (B6N) is becoming the standard background for genetic manipulation of the mouse genome. The B6N, whose genome is very closely related to the reference C57BL/6J genome, is versatile in a wide range of phenotyping and experimental settings and large repositories of B6N ES cells have been developed. Here, we present a series of studies showing the baseline characteristics of B6N fed a high-fat diet (HFD) for up to 12 weeks. We show that HFD-fed B6N mice show increased weight gain, fat mass, and hyperchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
35
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 67 publications
(80 reference statements)
16
35
1
2
Order By: Relevance
“…However, the impact of taurine on circadian clocks has not been studied before. In our results, HFD treatment significantly increased body weight and visceral fat and decreased glucose tolerance and insulin sensitivity, as previously established in other studies102021. Taurine treatment prevents increases in body weight, glucose intolerance, insulin resistance and reduced visceral fat, according to studies where taurine had several beneficial metabolic effects in different models of type 2 diabetes and obesity2223242526.…”
Section: Discussionsupporting
confidence: 90%
“…However, the impact of taurine on circadian clocks has not been studied before. In our results, HFD treatment significantly increased body weight and visceral fat and decreased glucose tolerance and insulin sensitivity, as previously established in other studies102021. Taurine treatment prevents increases in body weight, glucose intolerance, insulin resistance and reduced visceral fat, according to studies where taurine had several beneficial metabolic effects in different models of type 2 diabetes and obesity2223242526.…”
Section: Discussionsupporting
confidence: 90%
“…They developed obesity, dyslipidaemia and glucose intolerance; therefore, they can be considered a convenient rodent model for MetS. These results were consistent with those previously reported by Fraulop, Ogg-Diamantino, Fernandes-Santos, Barbosa, and Mandarim-de-Lacerda (2010) and Podrini et al (2013) who used mouse models after consumption of a HFD.…”
Section: Effect Of the Hfd On The Body Weight And Metabolic Parametersupporting
confidence: 90%
“…In contrast, final body weight, body weight gain, body weight gain per day, FER (percentages), and subcutaneous and visceral fat mass were lowered for the Xylo 5 and Xylo 10 groups compared with the HFD group. Previous studies have suggested that HFD-induced obesity alters lipid and blood glucose metabolism based on their analysis of metabolic parameters such as TC, LDL-C, and HDL-C [37,38]. Increased levels of TC and LDL-C, accompanied by low levels of HDL-C, are major risk factors for atherosclerosis and cardiovascular disease [39].…”
Section: Discussionmentioning
confidence: 99%